2002
DOI: 10.1038/sj.jhh.1001298
|View full text |Cite
|
Sign up to set email alerts
|

Sibutramine is safe and effective for weight loss in obese patients whose hypertension is well controlled with angiotensin-converting enzyme inhibitors

Abstract: Sibutramine treatment in obesity results in significantly greater weight reduction compared with placebo, although weight loss with sibutramine may be accompanied by small but statistically significant mean increases in blood pressure (BP). This 52-week, placebo-controlled, double-blind, randomised study investigated the effects of sibutramine 20 mg once daily or placebo on body weight in 220 obese (body mass index (BMI) 27-40 kg/m 2 ), hypertensive patients. At randomisation, hypertension was well controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0
4

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 17 publications
3
58
0
4
Order By: Relevance
“…65,66 The greatest improvements in glycemic control occurred in subjects with type 2 diabetes. 67,68 There were no significant effects of sibutramine therapy compared to diet-only therapy on lipids and glycemic control, but sibutramine was associated with higher systolic (1-4 mmHg) and diastolic (2-4 mmHg) blood pressure, 72,73,75,76 including subjects with treated hypertension. 73,75 Metformin had no effect on lipids or glycemic or blood pressure control in one study, 78 but in another study of subjects with impaired glucose tolerance, 77 metformin therapy conferred a 31% lower risk for type 2 diabetes.…”
Section: Jd Douketis Et Almentioning
confidence: 97%
See 1 more Smart Citation
“…65,66 The greatest improvements in glycemic control occurred in subjects with type 2 diabetes. 67,68 There were no significant effects of sibutramine therapy compared to diet-only therapy on lipids and glycemic control, but sibutramine was associated with higher systolic (1-4 mmHg) and diastolic (2-4 mmHg) blood pressure, 72,73,75,76 including subjects with treated hypertension. 73,75 Metformin had no effect on lipids or glycemic or blood pressure control in one study, 78 but in another study of subjects with impaired glucose tolerance, 77 metformin therapy conferred a 31% lower risk for type 2 diabetes.…”
Section: Jd Douketis Et Almentioning
confidence: 97%
“…No study reported on weight loss and its effects of cardiovascular risk factors in high-risk groups, unless the study was limited to high-risk subjects. 67,68,70,71,73,[75][76][77] …”
Section: Jd Douketis Et Almentioning
confidence: 99%
“…14 When hypertension is well controlled with medication, treatment with sibutramine results in reduced body weight with no adverse effects on blood pressure control. [15][16][17] Table 1 highlights what this study adds to what is already known about obesity and its risk factors.…”
Section: Introductionmentioning
confidence: 94%
“…At present only two drugs are approved for long-term use in the treatment of obesity, and both have troublesome side effects. The two papers 2,3 in this issue of the Journal of Human Hypertension focus on the effect of the anti-obesity drug sibutramine on the blood pressure of hypertensive patients treated for their hypertension.…”
mentioning
confidence: 99%
“…10 The observation that sibutramine, a drug that blocks the reuptake of noradrenaline and serotonin and to a lesser degree dopamine, raises blood pressure has been troubling. [11][12][13] We can get some insight into this problem and its importance from the two papers published in this issue of the Journal of Human Hypertension, 2,3 and another published elseCorrespondence: GA Bray, MD Pennington Biomedical Research Center, 6400 Perkins Road, Baton Rouge, LA 70808, USA. E-mail: BrayGAȰpbrc.edu where 14 that used sibutramine to treat the obesity in patients whose blood pressure was controlled with calcium channel blockers, with beta-blockers, or with angiotensin-converting enzyme inhibitors.…”
mentioning
confidence: 99%